Serum creatine kinase level is a poor predictor of muscle function after injury - Friden, J.; Lieber, R. L. (Scandinavian Journal of Medicine & Science in Sports, 2001)
Serum creatine kinase and dorsiflexion torque levels were measured in New Zealand White rabbits 1, 2, 7, 14, or 28 days after a single bout of eccentric exercise (n=26). No significant correlation was observed between creatine kinase activity and torque across time periods (P>0.15) and the regression relationship described only about 8% of the experimental variability. These data demonstrate that there exists a poor correlation between serum creatine kinase levels and skeletal muscle function after eccentric exercise.